DEVELOPMENT OF ALGORITHMS AND SOFTWARE COMPONENTS OF QUASI-STATIONARY MAGNETIC FIELDS MODELING - Ryabenkiy, V.; Chudaykin, I.; Targunakova, J. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The magnetometric section of the marine areas geophysics is characterized by the transition to a qualitatively new level of research, pipeline tracing, search for sunken ships, aerial bombs and unexploded ordnance, study of sunken objects of cultural heritage, identification of such sunken objects (inverse magnetometry problem), etc. The identification of such objects is called the inverse problem of marine magnetometry, and it belongs to the class of incorrectly posed task. The first step in solving this task is to find solution of the direct problem. A direct problem is to determine the anomalous field created by objects of a certain shape, density under certain conditions of immersion and accumulation of information about these objects. Problems of determining the anomalous field of a thin-walled objects are of particular interest. The solution to this problem is largely determined by the existence of an effective system of programs for solving three-dimensional direct magnetometry problems – finding the fields of typical objects (by using sets of such objects you can approximate real objects). The article describes the operation of the main algorithm and subroutines that are part of the main algorithm of the developed MBEM software for modeling the magnetic fields of thin-walled structures. MBEM is based on the developed modified boundary element method, based on the classical boundary element method and the secondary source method. Numerical verification has been carried out and the efficiency of the developed algorithms and software components has been established on the problems of calculating the magnetic field of thin-walled structures for which solutions are known. The example of the software complex work is given – the calculation of the resulting field of a thin-walled pipe, namely the simulation of the tension vector in the plane that is under the object at a distance of one half meter.